A method for the oxidation of cyclic olefins

CN117843468BActive Publication Date: 2026-10-16CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211216284.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-30
Publication Date
2026-10-16
Estimated Expiration
2042-09-30

AI Technical Summary

Technical Problem

但现有氧化过程腐蚀污染严重,如利用硝酸氧化

Benefits of technology

[0035] Through the above technical solution, the method disclosed herein, which uses a catalyst containing phosphorus-modified carbonitriding materials, can achieve the oxidation of cycloolefins under mild conditions and has high selectivity for the target product compared to a catalyst containing unmodified carbonitriding materials.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present disclosure relates to a method for the oxidation of cyclic alkenes, comprising: contacting a cyclic alkene and an oxidant with a catalyst comprising a phosphorus-modified carbon-nitrogen material to perform an oxidation reaction; wherein the phosphorus-modified carbon-nitrogen material is prepared by a method comprising the following steps: mixing a carbon-nitrogen material and an acid solution containing a phosphorus source, and then performing a hydrothermal treatment, and taking out the solid to obtain the phosphorus-modified carbon-nitrogen material. The method of the present disclosure can realize the oxidation of cyclic alkenes under mild conditions, and the selectivity of the target product is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to a method for the oxidation of cyclic olefins. Background Technology

[0002] Oxidation reactions of olefins play a vital role in chemical production, and the products of cycloolefin oxidation reactions play a unique role in modern chemical engineering. For example, the oxidation of cyclohexene to produce adipic acid is of great significance in chemical production. However, existing oxidation processes, such as those using nitric acid, cause severe corrosion and pollution.

[0003] There is an urgent need to develop environmentally friendly new technologies for existing cyclic olefin oxidation reactions. Summary of the Invention

[0004] The purpose of this invention is to provide a method for the oxidation of cyclic olefins, which has high feed conversion rate and high selectivity for target products.

[0005] To achieve the above objectives, this disclosure provides a method for oxidizing cyclic olefins, the method comprising: contacting the cyclic olefin and an oxidant with a catalyst containing a phosphorus-modified carbonitridium material to carry out an oxidation reaction;

[0006] The phosphorus-modified carbonitriding material is prepared by a method comprising the following steps:

[0007] The carbon-nitrogen material is mixed with an acid solution containing a phosphorus source and then subjected to hydrothermal treatment. The solid is then removed to obtain the phosphorus-modified carbon-nitrogen material.

[0008] Optionally, based on the dry weight of the carbonitriding material, the nitrogen content of the carbonitriding material is 30-75% by weight;

[0009] Based on the dry weight of the phosphorus-modified carbonitriding material, the phosphorus content in the phosphorus-modified carbonitriding material is 0.1-20% by weight.

[0010] Optionally, the weight ratio of the carbon-nitrogen material to the acid solution containing the phosphorus source is 1:(0.2-80), preferably 1:(2-40), and more preferably 1:(5-20);

[0011] Optionally, the acid solution containing the phosphorus source contains phosphorus element and acid;

[0012] In the acidic solution containing the phosphorus source, the content of the phosphorus source is 0.5-50% by weight, preferably 2-25% by weight, more preferably 4-20% by weight;

[0013] The acid content is 1-40% by weight, preferably 2-20% by weight;

[0014] The phosphorus source is selected from one or more of phosphoric acid, phosphorous acid, pyrophosphoric acid, metaphosphoric acid, and phosphorus pentoxide;

[0015] The acid is selected from one or more of phosphoric acid, hydrochloric acid, sulfuric acid, nitric acid, and phosphorous acid.

[0016] Optionally, the average particle size of the phosphorus-modified carbonitriding material is 20–800 nm, preferably 40–400 nm;

[0017] The phosphorus-modified carbonitriding material with a particle size of 40-100 nm accounts for 2-50% of the total weight of the phosphorus-modified carbonitriding material, preferably 4-40%, and more preferably 8-25%.

[0018] Optionally, the conditions for the hydrothermal treatment include: a temperature of 100–300°C and a time of 0.1–48 h;

[0019] The process of removing the solid to obtain the phosphorus-modified carbonitriding material includes: drying the removed solid to obtain the phosphorus-modified carbonitriding material;

[0020] The drying conditions may include: a temperature of 60–200°C and a time of 1–12 h; preferably, a temperature of 80–180°C and a time of 2–10 h.

[0021] Optionally, the carbon-nitrogen material is prepared by a method comprising the following steps:

[0022] The precursor containing nitrogen and carbon compounds was calcined at 500–1000 °C for 1–12 h under an inert atmosphere;

[0023] The precursor of the nitrogen-containing carbon compound is a nitrogen-containing carbon compound with a nitrogen content of 30-75% by weight;

[0024] Preferably, the precursor of the nitrogen-containing carbon compound is selected from one or more of urea, melamine, and melamine.

[0025] Optionally, the cyclic olefin is selected from substituted or unsubstituted cyclic olefins having 5-10 carbon atoms; the substituents in the substituted cyclic olefin are selected from one or more of halogen groups and alkyl groups having 1-5 carbon atoms;

[0026] Optionally, the cycloolefin is cyclohexene, cyclopentene, cyclooctene, cycloheptene, methylcyclohexene, halocyclopentene or halocyclohexene, or a combination of two or three of them.

[0027] The oxidant is an oxygen-containing gas, which is air or oxygen, and the molar ratio of the cyclic olefin to the oxygen in the oxygen-containing gas is 1:(1-15), preferably 1:(3-8).

[0028] Optionally, the method for oxidizing the cyclic olefin includes: contacting the cyclic olefin and the oxidant in the presence of a solvent and the catalyst to carry out the oxidation reaction;

[0029] The solvent is deionized water, a C1-C6 alcohol, a C3-C8 ketone, or a C2-C6 nitrile, or a combination of two or three of them.

[0030] The weight ratio of the cyclic olefin to the solvent is 1:(1-200), preferably 1:(5-100).

[0031] Optionally, the weight hourly space velocity of the cycloolefin is 0.2 to 200 h⁻¹. -1 Preferably 0.5 to 100 h -1 ;or,

[0032] Based on 100 mL of the cyclic olefin, the amount of catalyst used is 5 to 1000 mg, preferably 10 to 500 mg.

[0033] Optionally, the conditions for the oxidation reaction include: a temperature of 100–250°C, a pressure of 0.1–5 MPa, and a time of 1–24 h;

[0034] Preferably, the temperature is 120–220°C, the pressure is 0.2–2 MPa, and the time is 2–12 h.

[0035] Through the above technical solution, the method disclosed herein, which uses a catalyst containing phosphorus-modified carbonitriding materials, can achieve the oxidation of cycloolefins under mild conditions and has high selectivity for the target product compared to a catalyst containing unmodified carbonitriding materials.

[0036] Other features and advantages of this disclosure will be described in detail in the following detailed description section. Detailed Implementation

[0037] The following provides a detailed description of specific embodiments of this disclosure. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit this disclosure.

[0038] This disclosure provides a method for oxidizing cyclic olefins, the method comprising: contacting the cyclic olefin and an oxidant with a catalyst containing a phosphorus-modified carbonitridium material to carry out an oxidation reaction;

[0039] The phosphorus-modified carbonitriding material is prepared by a method comprising the following steps:

[0040] The carbon-nitrogen material is mixed with an acid solution containing a phosphorus source and then subjected to hydrothermal treatment. The solid is then removed to obtain the phosphorus-modified carbon-nitrogen material.

[0041] The target product of the oxidation of cycloolefins disclosed herein is a dicarboxylic acid.

[0042] According to one embodiment of this disclosure, the method for removing the solid is not specifically limited; for example, filtration, centrifugation, or other methods can be used. Preferably, the removed solid is dried. The drying conditions may include: a temperature of 60–200°C and a time of 1–12 hours; preferably, a temperature of 80–180°C and a time of 2–10 hours. Drying is a chemical operation well known to those skilled in the art, and can be carried out, for example, in a constant temperature drying oven or a muffle furnace.

[0043] According to one embodiment of this disclosure, based on the dry weight of the carbonitriding material, the nitrogen content of the carbonitriding material is 30-75% by weight, preferably 35-70% by weight; based on the dry weight of the phosphorus-modified carbonitriding material, the phosphorus content in the phosphorus-modified carbonitriding material is 0.1-20% by weight, preferably 0.5-10% by weight. The nitrogen content of the carbonitriding material and the phosphorus content in the phosphorus-modified carbonitriding material of this disclosure can be obtained by XPS method.

[0044] According to one embodiment of this disclosure, the catalyst may also contain other materials commonly used by those skilled in the art for the oxidation of cyclic olefins, such as one or more transition metal oxides, noble metals, and heteroatom molecular sieves. In a preferred embodiment, the catalyst is a 100% phosphorus-modified carbonitriding material.

[0045] According to one embodiment of this disclosure, carbonitriding materials can be obtained by calcining a precursor containing nitrogen-containing carbon compounds. The specific steps are as follows: The precursor containing nitrogen-containing carbon compounds is calcined in a sealed heat-resistant container under an inert atmosphere at 500–1000°C for 1–12 hours, preferably at 700–900°C for 2–6 hours. The sealed heat-resistant container can be any commonly used by those skilled in the art, such as a quartz tube, a quartz crucible (sealed with high-temperature vacuum grease), or a stainless steel reactor. The type of inert gas in the inert atmosphere is not specifically limited; it can be argon, helium, nitrogen, etc., and the inert gas content in the inert atmosphere is greater than 85% by volume, preferably greater than 90% by volume. Using the nitrogen-containing carbon compounds prepared by the above method in the oxidation process of cycloolefins can further improve the conversion rate of the raw materials and the selectivity for the target product. The precursor of the nitrogen-containing carbon compound is a nitrogen-containing carbon compound with a nitrogen content of 30-75% by weight; preferably, the precursor of the nitrogen-containing carbon compound is selected from one or more of urea, melamine, and melamine; more preferably, the precursor of the nitrogen-containing carbon compound is a nitrogen-containing carbon compound with a nitrogen content of 35-70% by weight, and more preferably urea. Calcination is a technique well known to those skilled in the art, and can be carried out in a muffle furnace or a tube furnace. This disclosure does not specifically limit the calcination atmosphere, which is generally an inert atmosphere, such as a carbon dioxide atmosphere, a nitrogen atmosphere, or an inert gas atmosphere.

[0046] According to this disclosure, the acid solution of the phosphorus source can be any form of dissolution or an acid solution containing phosphorus.

[0047] According to one embodiment of this disclosure, the phosphorus source is conventional in the art and can be various inorganic substances containing phosphorus elements, as well as non-toxic organic phosphorus sources such as phospholipids. Preferably, the phosphorus source is selected from one or more of phosphoric acid, phosphorous acid, pyrophosphoric acid, metaphosphoric acid, and phosphorus pentoxide; the acid is selected from one or more of phosphoric acid, hydrochloric acid, sulfuric acid, nitric acid, and phosphorous acid. Phosphoric acid and phosphorous acid can be used as both phosphorus source and acid at the same time, that is, the acid solution containing phosphorus source can be a phosphoric acid solution or a phosphorous acid solution.

[0048] According to one embodiment of this disclosure, the weight ratio of carbon-nitrogen material to acid solution containing phosphorus source can vary within a wide range, for example, it can be 1:(0.2 to 80), preferably 1:(2 to 40), and more preferably 1:(5 to 20). When the weight ratio of carbon-nitrogen material to acid solution containing phosphorus source is within the above range, phosphorus-modified carbon-nitrogen material with better catalytic performance can be prepared.

[0049] According to one embodiment of this disclosure, the content of phosphorus source in the acid solution containing phosphorus source can vary within a wide range, for example, it can be 0.5 to 50% by weight, preferably 2 to 25% by weight, more preferably 4 to 20% by weight; the content of acid is 1 to 40% by weight, preferably 2 to 20% by weight.

[0050] According to one embodiment of this disclosure, the average particle size of the carbonitriding material can be 20–800 nm, preferably 40–400 nm. In this disclosure, "particle size" refers to the distance between the two points on the particle with the largest distance. The inventors of this application have unexpectedly discovered that when the weight of the carbonitriding material with a particle size of 40–100 nm accounts for 2–50% of the total weight of the carbonitriding material, preferably 4–40%, and more preferably 8–25%, the phosphorus-modified carbonitriding material prepared within the above-mentioned preferred range exhibits superior catalytic oxidation performance of cyclic olefins. The phosphorus-modified carbonitriding material of this disclosure has suitable particle size and excellent catalytic performance, and is particularly suitable for the catalytic oxidation of cyclic olefins.

[0051] According to one embodiment of this disclosure, the conditions for hydrothermal treatment may include: a temperature of 100–300°C and a time of 0.1–48 h; preferably, a temperature of 150–250°C and a time of 2–24 h. The pressure for hydrothermal treatment is not specifically limited and can be either self-generated pressure or applied pressure, preferably under self-generated pressure.

[0052] According to one embodiment of this disclosure, the cyclic olefin is selected from substituted or unsubstituted cyclic olefins having 5-10 carbon atoms; the substituents in the substituted cyclic olefin are selected from one or more of halogen groups and alkyl groups having 1-5 carbon atoms; preferably, the cyclic olefin is cyclohexene, cyclopentene, cyclooctene, cycloheptene, methylcyclohexene, halocyclopentene or halocyclohexene, or a combination of two or three of them.

[0053] According to one embodiment of this disclosure, the oxidant is an oxygen-containing gas, which is air or oxygen, and the molar ratio of the cyclic olefin to the oxygen in the oxygen-containing gas is 1:(1-15), preferably 1:(3-8).

[0054] To improve the homogeneity among reactants, according to one embodiment of this disclosure, the method for oxidizing cycloolefins may include: contacting a cycloolefin and an oxidant in the presence of a solvent and a catalyst to carry out an oxidation reaction. The solvent may be any liquid capable of dissolving the cycloolefin and peroxide or promoting their mixing, and also promoting the dissolution of the target product, such as an organic solvent and / or deionized water. The organic solvent is well known to those skilled in the art, and may be, for example, C1-C6 alcohols, C3-C8 ketones, or C2-C6 nitriles, or combinations of two or three thereof. Preferably, the solvent is one or more of methanol, acetone, and deionized water. The weight ratio of the cycloolefin to the solvent may vary over a wide range, for example, 1:(1-200), preferably 1:(5-100), and more preferably 1:(5-50).

[0055] According to one embodiment of this disclosure, the oxidation reaction can be carried out in any catalytic reactor well known to those skilled in the art, such as a batch reactor, fixed-bed reactor, moving-bed reactor, suspended-bed reactor, or slurry-bed reactor. In one specific embodiment, the catalytic oxidation reaction is carried out in a fixed-bed reactor, and the weight hourly space velocity (WHSV) of the cycloolefin is 0.2–200 h⁻¹. -1 Preferably 0.5 to 100 h -1 In another specific embodiment, the catalytic oxidation reaction is carried out in a slurry bed reactor, and the amount of catalyst used is 5 to 1000 mg, preferably 10 to 500 mg, and more preferably 20 to 250 mg, based on 100 mL of cycloolefins.

[0056] According to one embodiment of this disclosure, the conditions for the oxidation reaction may include: a temperature of 100–250°C, a pressure of 0.1–5 MPa, and a time of 1–24 h; preferably, a temperature of 120–220°C, a pressure of 0.2–2 MPa, and a time of 2–12 h.

[0057] In a preferred embodiment, the oxidation reaction is carried out under stirring conditions. The specific form of stirring is not limited, and any common stirring method is acceptable, such as mechanical stirring or magnetic stirring.

[0058] The present disclosure will be further illustrated by the following examples, but the present disclosure is not limited thereto.

[0059] All reagents used in the examples and comparative examples were of analytical grade and were commercially available.

[0060] In the preparation examples, the average particle size (particle diameter) of the carbonitriding materials was determined using FEI's TECNAIG standard. 2The measurements were performed using an F20 (200kV) transmission electron microscope. The test conditions were as follows: accelerating voltage 20kV, sample preparation using the suspension method, placing the sample in a 2mL glass bottle, dispersing it with anhydrous ethanol, shaking it until homogeneous, taking one drop with a dropper and dropping it onto a 3mm diameter sample grid, allowing it to dry, placing it in the sample injector, and then inserting it into the electron microscope for observation. 100 carbon-nitrogen material particles were randomly selected for particle size statistics.

[0061] The proportion of carbon-nitrogen materials with particle sizes in the range of 40–100 nm was determined by separating particles with particle sizes in the range of 40–100 nm using a membrane separation device (model BONA-GM-05) from Jinan Bona Biotechnology Co., Ltd. Then, based on the weight of the separated carbon-nitrogen materials with particle sizes in the range of 40–100 nm and the total weight of the carbon-nitrogen materials, the ratio of the weight of carbon-nitrogen materials with particle sizes in the range of 40–100 nm to the total weight of the carbon-nitrogen materials was calculated.

[0062] The nitrogen and phosphorus content was determined using X-ray photoelectron spectroscopy (XPS) on a VGESCA-LABS X-ray photoelectron spectrometer. This method is primarily used to analyze the state of elements on the sample surface and the interactions between elements. Test conditions: Mg Kα rays were used as the laser source (hν = 1253.6 eV, detection sensitivity > 1%, vacuum degree 10). -7 Pa).

[0063] The preparation examples illustrate the phosphorus-modified carbonitriding materials prepared by the method of the present invention, while the preparation comparative examples illustrate the carbonitriding materials prepared by methods in the prior art.

[0064] Preparation Example 1

[0065] In a nitrogen atmosphere, 50g of urea was placed in a 100mL crucible, sealed with a vacuum sealant, and then calcined in a muffle furnace at 700℃ for 3 hours. After natural cooling at room temperature (20℃, the same below), a carbonitriding material (nitrogen content of 56% by weight) was obtained. The carbonitriding material was then added to a phosphoric acid aqueous solution (concentration of 5% by weight) and mixed. The weight ratio of carbonitriding material to phosphoric acid aqueous solution was 1:5. The mixture was then subjected to hydrothermal treatment at 200℃ for 12 hours and then dried at 120℃ for 6 hours to obtain a phosphorus-modified carbonitriding material A1 with a phosphorus content of 1.7% by weight.

[0066] The average particle size of the phosphorus-modified carbonitriding material A1 is 310 nm, of which the carbonitriding material with a particle size of 40-100 nm accounts for 24% of the total weight of the carbonitriding material.

[0067] Preparation Example 2

[0068] In a nitrogen atmosphere, 40g of urea was placed in a 100mL crucible, sealed with a vacuum sealant, and calcined in a muffle furnace at 800℃ for 5h. After natural cooling at room temperature, a carbonitridinium material (nitrogen content of 63 wt%) was obtained. The carbonitridinium material was then mixed with a phosphoric acid aqueous solution (concentration of 10 wt%) at a weight ratio of 1:10. The mixture was then subjected to hydrothermal treatment at 150℃ for 12h and dried at 100℃ for 6h to obtain phosphorus-modified carbonitridinium material A2 with a phosphorus content of 5.3 wt%.

[0069] The average particle size of the phosphorus-modified carbonitriding material A2 is 160 nm, of which carbonitriding materials with a particle size of 40–100 nm account for 21% of the total weight of the carbonitriding material.

[0070] Preparation Example 3

[0071] In a nitrogen atmosphere, 100g of urea was placed in a 200mL crucible, sealed with a vacuum sealant, and calcined in a muffle furnace at 550℃ for 8 hours. After natural cooling to room temperature, a carbonitriding material (nitrogen content of 53% by weight) was obtained. The carbonitriding material was then added to a phosphoric acid aqueous solution (concentration of 5% by weight) and mixed. The weight ratio of carbonitriding material to phosphoric acid aqueous solution was 1:20. The mixture was then subjected to hydrothermal treatment at 100℃ for 24 hours and dried at 120℃ for 6 hours to obtain a phosphorus-modified carbonitriding material A3 with a phosphorus content of 1.1% by weight.

[0072] The average particle size of the phosphorus-modified carbonitriding material A3 is 60 nm, of which carbonitriding materials with particle sizes of 40–100 nm account for 41% of the total weight of the carbonitriding material.

[0073] Preparation Example 4

[0074] In a nitrogen atmosphere, 60g of melamine was placed in a 100mL crucible, sealed with a vacuum sealant, and calcined in a muffle furnace at 900℃ for 2 hours. After natural cooling at room temperature, a carbonitriding material (nitrogen content of 67 wt%) was obtained. The carbonitriding material was then added to a phosphoric acid aqueous solution (concentration of 0.5 wt%) and mixed. The weight ratio of carbonitriding material to phosphoric acid aqueous solution was 1:15. The mixture was then subjected to hydrothermal treatment at 280℃ for 6 hours and dried at 150℃ for 6 hours to obtain a phosphorus-modified carbonitriding material A4 with a phosphorus content of 0.6 wt%.

[0075] The average particle size of the phosphorus-modified carbonitriding material A4 is 520 nm, of which carbonitriding materials with a particle size of 40-100 nm account for 3% of the total weight of the carbonitriding material.

[0076] Preparation Example 5

[0077] In a nitrogen atmosphere, 50g of urea was placed in a 100mL crucible, sealed with a vacuum sealant, and then calcined in a muffle furnace at 650℃ for 6 hours. After natural cooling at room temperature (20℃, the same below), a carbonitriding material (nitrogen content of 55% by weight) was obtained. The carbonitriding material was then added to a phosphorous acid solution (concentration of 5% by weight) and mixed. The weight ratio of carbonitriding material to aqueous solution was 1:5. The mixture was then subjected to hydrothermal treatment at 200℃ for 12 hours and then dried at 120℃ for 6 hours to obtain a phosphorus-modified carbonitriding material A5 with a phosphorus content of 2.1% by weight.

[0078] The average particle size of the phosphorus-modified carbonitriding material A5 is 180 nm, of which carbonitriding materials with a particle size of 40–100 nm account for 9% of the total weight of the carbonitriding material.

[0079] Preparation Example 6

[0080] In a nitrogen atmosphere, 50g of melamine was placed in a 100mL crucible, sealed with a vacuum sealant, and calcined in a muffle furnace at 1000℃ for 1h. After natural cooling at room temperature (20℃, the same below), a carbonitriding material (nitrogen content of 69 wt%) was obtained. The carbonitriding material was then added to a phosphoric acid aqueous solution (concentration of 5 wt%) and mixed. The weight ratio of carbonitriding material to phosphoric acid aqueous solution was 1:5. The mixture was then subjected to hydrothermal treatment at 280℃ for 12h and dried at 120℃ for 6h to obtain a phosphorus-modified carbonitriding material A6 with a phosphorus content of 2.2 wt%.

[0081] The average particle size of the phosphorus-modified carbonitriding material A6 is 620 nm, of which carbonitriding materials with particle sizes of 40–100 nm account for 4% of the total weight of the carbonitriding material.

[0082] Preparation Example 7

[0083] In a nitrogen atmosphere, 50g of urea was placed in a 100mL crucible, sealed with a vacuum sealant, and calcined in a muffle furnace at 450℃ for 8 hours. After natural cooling at room temperature, a carbonitriding material (nitrogen content of 51% by weight) was obtained. The carbonitriding material was then mixed with a phosphoric acid aqueous solution (concentration of 5% by weight) at a weight ratio of 1:5. The mixture was then subjected to hydrothermal treatment at 200℃ for 12 hours and dried at 120℃ for 6 hours to obtain a phosphorus-modified carbonitriding material A7 with a phosphorus content of 21% by weight.

[0084] The average particle size of the phosphorus-modified carbonitriding material A7 is 19 nm, of which the weight of carbonitriding material with a particle size of 40-100 nm accounts for 0% of the total weight of carbonitriding material.

[0085] Preparation of Comparative Example 1

[0086] In a nitrogen atmosphere, 50g of urea was placed in a 100mL crucible, covered and sealed with vacuum sealant. The crucible was then placed in a muffle furnace at 450℃ and calcined for 8 hours. After natural cooling at room temperature, carbon-nitrogen material particles a (nitrogen content of 51% by weight) were obtained.

[0087] The average particle size of carbonitriding material particle a is 400 nm, and the weight of carbonitriding material with a particle size of 40-100 nm accounts for 1% of the total weight of carbonitriding material.

[0088] The examples illustrate the method for oxidizing cycloolefins according to the present invention.

[0089] In the following examples and comparative examples, gas chromatography (GC: Agilent, 7890A) and gas chromatography-mass spectrometry (GC-MS: Thermo Fisher Trace ISQ) were used to analyze the oxidation products.

[0090] The following formulas are used to calculate the feed conversion rate and target product selectivity:

[0091] Cyclic olefin conversion % = (molar amount of cyclic olefin added before reaction - molar amount of cyclic olefin remaining after reaction) / molar amount of cyclic olefin added before reaction × 100%.

[0092] Target product selectivity % = (molar amount of target product generated after reaction) / molar amount of cyclic olefin added before reaction × 100%.

[0093] Example 1

[0094] 80 mL of cyclohexene and 0.25 g of phosphorus-modified carbon-nitrogen material A1 were added as catalysts to a 250 mL high-pressure reactor. After forming the reaction mixture, the reactor was sealed, and oxygen (oxygen to cyclohexene molar ratio of 8:1) was introduced. The mixture was stirred at 130 °C and 2 MPa for 2 h, and then the catalyst was separated by centrifugation and filtration. The results of the analysis of the obtained oxidation products are listed in Table 1.

[0095] Examples 2-7

[0096] Cyclohexene was oxidized according to the method of Example 1, except that the same amount of phosphorus-modified carbon-nitrogen materials A2-A7 were used instead of A1 as catalyst. The results of the analysis of the oxidation products are listed in Table 1.

[0097] Example 8

[0098] Cyclohexene was introduced into the reaction zone from the top inlet of a small-scale laboratory fixed-bed reactor, while oxygen was introduced from the bottom inlet. The cyclohexene was then contacted with a phosphorus-modified carbonitriding material, Al, which served as a catalyst. The molar ratio of cyclohexene to oxygen was 1:4. The reaction temperature was 120°C, the pressure was 0.8 MPa, and the weight hourly space velocity (WHSV) of cyclohexene was 2 h⁻¹. -1 The reaction mixture was subjected to online gas chromatography analysis after 2 hours, and the results are listed in Table 1.

[0099] Example 9

[0100] Cyclohexene was oxidized according to the method of Example 1, except that acetone was added to the reaction vessel as a solvent, and the weight ratio of cyclohexene to solvent was 1:5. The results are listed in Table 1.

[0101] Comparative Example 1

[0102] Cyclohexene was oxidized according to the method of Example 1, except that no phosphorus-modified carbon-nitrogen material was added as a catalyst. The results of the analysis of the oxidation products are listed in Table 1.

[0103] Comparative Example 2

[0104] Cyclohexene was oxidized according to the method of Example 1, except that α was added as a catalyst. The results of the analysis of the oxidation products are listed in Table 1.

[0105] Table 1

[0106] Example 1 A1 46 88 Example 2 A2 35 83 Example 3 A3 31 73 Example 4 A4 29 71 Example 5 A5 38 79 Example 6 A6 34 75 Example 7 A7 25 69 Example 8 A1 27 90 Example 9 A1 48 85 Comparative Example 1 - 4 62 Comparative Example 2 a 22 65

[0107] As shown in Table 1, the cyclohexene oxidation method of this disclosure has a higher feed conversion rate and adipic acid selectivity as the target product. Furthermore, a comparison of Examples 3, 4, 6, and 7 with Examples 1, 2, and 5 shows that when the weight of carbonitriding materials with particle sizes of 40–100 nm accounts for 8–25% of the total weight of the carbonitriding materials, the phosphorus-modified carbonitriding materials exhibit superior catalytic performance for the oxidation of cycloolefins.

[0108] The preferred embodiments of this disclosure have been described in detail above. However, this disclosure is not limited to the specific details of the above embodiments. Within the scope of the technical concept of this disclosure, various simple modifications can be made to the technical solutions of this disclosure, and these simple modifications all fall within the protection scope of this disclosure.

[0109] It should also be noted that the various specific technical features described in the above embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, this disclosure will not describe the various possible combinations separately.

[0110] Furthermore, various different embodiments of this disclosure can be combined in any way, as long as they do not violate the spirit of this disclosure, they should also be regarded as the content disclosed in this disclosure.

Claims

1. A method for oxidizing cycloolefins, characterized in that, The method includes: contacting cycloolefins and an oxidant with a catalyst containing phosphorus-modified carbonitridium materials to carry out an oxidation reaction; The phosphorus-modified carbonitriding material is prepared by a method comprising the following steps: The carbon-nitrogen material is mixed with an acid solution containing a phosphorus source and then subjected to hydrothermal treatment. The solid is then removed to obtain the phosphorus-modified carbon-nitrogen material. The acid solution containing the phosphorus source contains phosphorus and acid; The phosphorus source is selected from one or more of phosphoric acid, phosphorous acid, pyrophosphoric acid, metaphosphoric acid, and phosphorus pentoxide; The acid is selected from one or more of phosphoric acid, hydrochloric acid, sulfuric acid, nitric acid, and phosphorous acid; The carbon-nitrogen material is prepared by a method comprising the following steps: The precursor containing nitrogen and carbon compounds was calcined at 500-1000℃ for 1-12 hours under an inert atmosphere. The precursor of the nitrogen-containing carbon compound is selected from one or more of urea, melamine and melamine; The average particle size of the phosphorus-modified carbonitridium material is 20~800 nm; The phosphorus-modified carbonitriding material with a particle size of 40-100 nm accounts for 2-50% of the total weight of the phosphorus-modified carbonitriding material.

2. The method according to claim 1, wherein, Based on the dry weight of the carbonitriding material, the nitrogen content of the carbonitriding material is 30-75% by weight. Based on the dry weight of the phosphorus-modified carbonitriding material, the phosphorus content in the phosphorus-modified carbonitriding material is 0.1~20% by weight.

3. The method according to claim 1, wherein, The weight ratio of the carbonitriding material to the acid solution containing the phosphorus source is 1:(0.2~80). In the acidic solution containing the phosphorus source, the content of the phosphorus source is 0.5-50% by weight. The acid content is 1-40% by weight.

4. The method according to claim 1, wherein, The weight ratio of the carbon-nitrogen material to the acid solution containing the phosphorus source is 1:(2~40).

5. The method according to claim 1, wherein, The weight ratio of the carbon-nitrogen material to the acid solution containing the phosphorus source is 1:(5~20).

6. The method according to claim 1, wherein, In the acid solution containing the phosphorus source, the content of the acid is 2 to 20% by weight.

7. The method according to claim 1, wherein, In the acidic solution containing the phosphorus source, the content of the phosphorus source is 2-25% by weight.

8. The method according to claim 1, wherein, In the acidic solution containing the phosphorus source, the content of the phosphorus source is 4-20% by weight.

9. The method according to claim 1, wherein, The average particle size of the phosphorus-modified carbonitridium material is 40~400nm; The phosphorus-modified carbonitriding material with a particle size of 40-100 nm accounts for 4-40% of the total weight of the phosphorus-modified carbonitriding material.

10. The method according to claim 1, wherein, The phosphorus-modified carbonitriding material with a particle size of 40-100 nm accounts for 8-25% of the total weight of the phosphorus-modified carbonitriding material.

11. The method according to claim 1, wherein, The conditions for the hydrothermal treatment include: a temperature of 100~300℃ and a time of 0.1~48h; The process of removing the solid to obtain the phosphorus-modified carbonitriding material includes: drying the removed solid to obtain the phosphorus-modified carbonitriding material; The drying conditions may include a temperature of 60~200℃ and a time of 1~12h.

12. The method according to claim 11, wherein, The drying conditions may include: a temperature of 80~180℃ and a time of 2~10h.

13. The method according to claim 1, wherein, The cyclic olefin is selected from substituted or unsubstituted cyclic olefins having 5-10 carbon atoms in the ring; the substituents in the substituted cyclic olefin are selected from one or more of halogen groups and alkyl groups having 1-5 carbon atoms; The oxidant is an oxygen-containing gas, which is air or oxygen, and the molar ratio of the cyclic olefin to the oxygen in the oxygen-containing gas is 1:(1~15).

14. The method according to claim 13, wherein, The molar ratio of the cyclic olefin to the oxygen in the oxygen-containing gas is 1:(3~8).

15. The method according to claim 1, wherein, The cycloolefin is cyclohexene, cyclopentene, cyclooctene, cycloheptene, methylcyclohexene, halocyclopentene, or a combination of two or three of them.

16. The method according to claim 1, wherein, The method for oxidizing cyclic olefins includes: contacting the cyclic olefin and the oxidant in the presence of a solvent and the catalyst to carry out the oxidation reaction; The solvent is deionized water, a C1-C6 alcohol, a C3-C8 ketone, or a C2-C6 nitrile, or a combination of two or three of them. The weight ratio of the cyclic olefin to the solvent is 1:(1~200).

17. The method according to claim 16, wherein, The weight ratio of the cyclic olefin to the solvent is 1:(5~100).

18. The method according to claim 1, wherein, The weight hourly space velocity of the cycloolefin is 0.2~200 h⁻¹. -1 ; or, Based on 100 mL of the cyclic olefin, the amount of catalyst used is 5 to 1000 mg.

19. The method according to claim 1, wherein, The weight hourly space velocity of the cycloolefin is 0.5~100 h⁻¹. -1 .

20. The method according to claim 1, wherein, Based on 100 mL of the cyclic olefin, the amount of catalyst used is 10-500 mg.

21. The method according to claim 1, wherein, The conditions for the oxidation reaction include: a temperature of 100~250℃, a pressure of 0.1~5MPa, and a time of 1~24h.

22. The method according to claim 1, wherein, The conditions for the oxidation reaction include: a temperature of 120~220℃, a pressure of 0.2~2MPa, and a time of 2~12h.

Citation Information

Patent Citations

  • Catalytic oxidation method of cyclic hydrocarbon

    CN111099983A

  • Cycloalkane oxidation method

    CN113582831A